16 SOCS1 box evoked expression in mechanically strained cultured mice ventricle myocardium. (March 2019) - Chen, C; Kwabena, B; Shen, ZH; Wang, H; Chen, J; Chang, CC; Zhang, ZY; Pokuaa, D; He, T; Gao, LF; Cheng, ZB; Wang, Y
Abstract : Background: This study investigated SOCS1 box expression in mechanically strained ventricular myocardium in culture transfection preparations. Methods: The left ventricle anterior wall strip in mice was mechanically loaded by length stretching during tissue culture. While constructing the SOCS1 vector, intransfection preparations were also carried out. The preparations of mechanically strained cultures continued for 72 hours. After total proteins were extracted, SDS-PAGE assay was used for evaluating 25 kDa band optical density in the cultured preparations. SOCS1box specific expression optical density was calculated in western blot transfer membrane. Results: The total proteins in 25 kDa band were highly expressed in transfection preparations; however, mechanical strain induced increased 25 kDa expression but not significantly. SCOS1 box protein was significantly increased in strained but not in transfection preparations. Furthermore, SCOS1 box expression occurred in the precipitate rather than in the supernatant of strain cultured preparations. Conclusion: SOCS1 box protein is mechanically strained cellular signaling which is expressed in mechanically strained cultured mice ventricular myocardium. Transfection alone does not make a significant expression in this model, but combination with mechanical straining can dramatically increase nuclear SOCS1 box protein in cultured ventricular myocardium. Acknowledgements: Supported by project grant from Hainan Medical College Undergraduate Training Programs for Innovation and Entrepreneurship (HYCX2018068), Hainan Key Research and Development project (ZDYF2017121).